Bookworm a neural net approach to optical character recognition - Biado, Daniel Manansala; Marges, Christopher Andrade; Reyes, Vincintz Theo Balajadia; Tiama, Aristotle Campos (1999)
Books are the primary medium of information nowadays. Be it scientific, political or about arts, you can find the information you need in books, journals and manuals among any other paper-based mediaums. However, reading books can sometimes be an agonizing experience specially if the book you are reading is not your field of interest. This can sometimes be a problem. Not only does it inhibit learning in an individual, it has psychological effects too. Bookworm is our proposed solution to thi problem. Simply put, Bookworm is a program that scans a page of text and reads it to you in monotonic voice. Also, by listening, learning rate is constant whereas eye fatigue could decrease your pace when you, are just reading. As an afterthought, Bookworm could also help people with optical difficulty. Specialized books (e.g. Braille) could cost a lot of money to fabricate. Using Bookworm, the blind need not be deprived of learning a certain book that is not available for them. All they do is run it under a scanner (flatbed preferably) and they are on their way to learning. It is amazing to think that such a simple software could have tremendous and far-reaching benefits.
Thesis (B.S. Computer Science)--University of the Philippines Diliman.
Keywords: Text-to-speech software; Optical character recognition